Adsorption of Cutting Fluid from Turning Process by Using Modified Sugarcane Bagasse as Adsorbent - ปิยะมังคลา โกวิทย์ (Srinakharinwirot University Engineering Journal, 2018)
The modified sugarcane bagasse was used as an adsorbent for eliminate of cutting fluid from turning process. The effects of mass of adsorbent and initial concentration of cutting fluid were thoroughly investigated in batch adsorption systems. It was found that the point of zero charge of modified sugarcane bagasse was pH 1.6. Increasing in mass of adsorbents and initial cutting fluid concentrations increased the percent adsorption and adsorption capacity, respectively. The highest adsorption capacity, 501.7 mg/g, was obtained at 5.0 g and 49,797 mg/L for mass of modified sugarcane bagasse and initial concentration of cutting fluid, respectively. The Langmuir adsorption was rather fitted for describing the isotherm than Freundlich model. Batch designs of modified sugarcane bagasse for removal 100% of turning process wastewater amount 1 L was 0.24 g.